1977
DOI: 10.1159/000231843
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Crude Timothy Grass Pollen Extract

Abstract: Timothy pollen extracts have been reacted with glutaraldehyde under conditions leading to different degrees of aggregation of the product. Aggregation tends to enhance the previously demonstrated effects of glutaraldehyde in that reactivity with human IgE antibody, and ability to induce IgE antibody in the Bordetella pertussis-treated rat, are further reduced. Ability to induce IgG antibody with specificity for unmodified extract is substantially retained in all aggregated products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The test article consists of pollen extract from 13 species of grass chemically modified with glutaraldehyde (forming an allergoid) adsorbed to L-tyrosine, a naturally occurring amino acid in a microcrystalline form with the addition of the adjuvant MPL ® , a detoxified derivative of lipid A of Salmonella minnesota R595. It has been shown that modification of allergen to allergoid reduces IgE reactivity with retention of IgG binding epitopes as shown from immunoreactivity and structural analysis testing with single or multiple mix grass allergoids (Moran, Wheeler, Overell, & Woroniecki, 1977;Starchenka, Bell, Mwange, Skinner, & Heath, 2017). Adjuvant use of microcrystalline tyrosine (MCT) allows controlled slow release of allergoid resulting in reduced incidence of local IgE-mediated allergic responses, while prolonging the antigenic response of the therapy (Leuthard et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The test article consists of pollen extract from 13 species of grass chemically modified with glutaraldehyde (forming an allergoid) adsorbed to L-tyrosine, a naturally occurring amino acid in a microcrystalline form with the addition of the adjuvant MPL ® , a detoxified derivative of lipid A of Salmonella minnesota R595. It has been shown that modification of allergen to allergoid reduces IgE reactivity with retention of IgG binding epitopes as shown from immunoreactivity and structural analysis testing with single or multiple mix grass allergoids (Moran, Wheeler, Overell, & Woroniecki, 1977;Starchenka, Bell, Mwange, Skinner, & Heath, 2017). Adjuvant use of microcrystalline tyrosine (MCT) allows controlled slow release of allergoid resulting in reduced incidence of local IgE-mediated allergic responses, while prolonging the antigenic response of the therapy (Leuthard et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…I would agree with the authors that there are some grounds for suggesting that such modified allergens might have utility as therapeutic allergy vaccines. I would, however, suggest to the authors that they consider some evidence published in a series of earlier articles by us ( 2–4) before proceeding to clinical evaluation of their materials.…”
mentioning
confidence: 99%